SHARK AND BOT. 2 : Sleepaway Champs - Yanish, Brian (New York, United States : Random House Children's Books, 2021)
Shark and Bot, the two most unlikely friends, are back for more hilarious and epic adventures! It's Summer vacation and Shark and Bot have a new adventure-- at sleepaway camp! Shark (always a nervous nelly!) quickly starts feeling homesick. Can he make it through the week? Will Bot short circuit at the lake? Find out in this hilarious new installment.
Keywords: Comic books, strips, etc -- United States; Children's stories, fiction